Perancangan Rencana Keberlangsungan Bisnis dalam Manajemen Risiko Layanan Teknologi Informasi - Handoko, Handoko; Elly, Elly (Maranatha University Press, 2023)
Universitas Mikroskil is one of the universities in Medan City that implements information technology in its business processes such as academic services for lecturers, students, education staff, administration and student data storage, lecturers, education staff,, and so on, financial processes, lecture processes, academic guidance, lecture scheduling, student attendance attendance, study plan card filling, schedule announcements, exam announcements, grade announcements, admissions, library management and so on. Seeing the many processes at Universitas Mikroskil, a disaster management plan is needed that can be used at the managerial level to anticipate the occurrence of unwanted things such as loss of important data or documents, viruses on computers or servers, and so on. The purpose of this study is to analyze and assess the risks and impacts of risks at Universitas Mikroskil. Furthermore, a business continuity plan is prepared based on an analysis of business risks and impacts to overcome information technology that is constrained by the disaster risk that occurs. Risk assessment on two natural threats has Vital criticality. The risk assessment on the three human threats has 1 Critical-Mission criticality, 1 Vital criticality, and 1 Minor criticality. The risk assessment on three infrastructure threats has 1 Critical-Mission criticality, and 2 Vital criticality. Risk assessment on three IT system threats has 2 Critical-Mission criticality, and 1 Vital criticality. From 8 operational activities, there are 5 Critical-Mission services, 2 Vital services, 1 Important service.